Comparative Study of Negative Pressure Wound Therapy and Silver-releasing Foam Dressings in the Management of Diabetic Foot Ulcers - Ali, Mian Amad; Husnain, Syed Shehzad; Shah, Muhammad Yousaf; Akram, Muhammad Waqas; Ansar, Fahad Raza; Hashmi, Syed Daood (Indus Journal of Bioscience Research, 2025)
Introduction: Diabetic foot ulcers (DFUs) can be defined as a major complication of Diabetes Mellitus that often results in infections and amputations. Wound care is of outmost importance, for with appropriate management, further problems do not occur and the wound heals. Negative Pressure Wound Therapy (NPWT) and silver-releasing foam dressings are two of the modalities of management of DFUs. Objectives: This proposal sought to determine the effectiveness of NPWT and silver-releasing foam dressings in the healing of diabetic foot ulcers and in the reduction of ulcer size over a six-week period. Materials and Methods: This study was quasi-experimental, and 120 patients across the PNS Hafeez Hospital in Islamabad were selected. Patients were randomly allocated to either the NPWT group or the silver-releasing foam dressing group. They include the time taken for the wounds to heal and the reduction of the size of the ulcer over a period of six weeks. Results: NPWT achieved a faster healing time in the study period of 19.7 days and had a greater percentage of mean ulcer area reduction, 38.7%, than the silver-releasing foam dressing of 24.9 days and 26.5%, respectively. Conclusion: This study confirms that Negative Pressure Wound Therapy (NPWT) is more effective than silver-releasing foam dressings in reducing DFU size and accelerating healing. NPWT promotes faster re-epithelialization due to its vacuum effect. However, drug-releasing foam dressings remain beneficial, especially when NPWT is unavailable. Treatment choice should consider patient needs and resources. Further research with larger samples and longer observation is needed to validate these findings and assess long-term impacts.